Association of Symptomatic Benign Prostatic Hyperplasia and Prostate Cancer: Results from the Prostate Cancer Prevention Trial - Schenk, Jeannette M. (Oxford University Press, 2011)
This study examined the association between symptomatic benign prostatic hyperplasia (BPH) and prostate cancer risk in 5,068 placebo-arm participants enrolled in the Prostate Cancer Prevention Trial (1993–2003). These data include 1,225 men whose cancer was detected during the 7-year trial—556 detected for cause (following abnormal prostate-specific antigen or digital rectal examination) and 669 detected not for cause (without indication), as well as 3,843 men who had biopsy-proven absence of prostate cancer at the trial end. Symptomatic BPH was assessed hierarchically as self-report of surgical or medical treatment, moderately severe symptoms (International Prostate Symptom Score >14), or physician diagnosis, and analyses were completed by BPH status at baseline (prevalent) or BPH prior to cancer diagnosis or study end (prevalent plus incident). Controlled for age, race, and body mass index, neither prevalent (risk ratio = 1.03, 95% confidence interval: 0.92, 1.14) nor prevalent plus incident (risk ratio = 0.96, 95% confidence interval: 0.87, 1.06) symptomatic BPH was associated with prostate cancer risk. This lack of association was consistent across subgroups defined by type of BPH-defining event (treatment, symptoms, or physician diagnosis), prompt for prostate cancer diagnosis, and prostate cancer grade. This study provides the strongest evidence to date that BPH does not increase the risk of prostate cancer.